Reticulocyte count and exercise performance in elite athletes: A retrospective study - Ashikaga, K.; Perrone, M. A.; Gianfelici, A.; Ortolina, D.; Crotta, S.; Spinelli, A.; Monosilio, S.; Di Gioia, G.; Maestrini, V.; Squeo, M. R.; Pelliccia, A. (Sports, 2025)
Athletes engaged in dynamic sports experience a shortened red blood cell (RBC) lifespan and accelerated turnover due to RBC destruction. This accelerated RBC turnover might have a positive impact on exercise performance by increasing the number of young red blood cells with a high oxygen-carrying capacity. However, accelerated turnover might also be a result of intravascular haemolysis caused by RBC destruction during exercise, impairing RBC function and oxygen transport. Therefore, we aimed to evaluate the relationship between reticulocyte count as an indicator of short-term RBC profile changes and exercise capacity. We retrospectively evaluated elite Italian athletes engaged in endurance or mixed sports disciplines selected for the 2023 European Games or 2024 Olympic Games. Athletes underwent blood tests, echocardiography, and cardiopulmonary exercise tests. We assessed the relationship between reticulocytes and the peak value of VO2 (peak VO2) and anaerobic threshold (AT). In addition, the effects of age, sex, haemoglobin concentration, stroke volume, peak heart rate, and reticulocytes on peak VO2 and AT were assessed using multiple linear regression. Of the 105 athletes, reticulocyte count (0.059 ± 0.024 × 1012/L) negatively correlated with peak VO2 (45.5 ± 9.1 mL/min/kg) (p = 0.022) and AT (27.6 ± 7.9 mL/min/kg) (p = 0.040). Using multivariate linear regression analysis, reticulocytes were independent predictors of peak VO2 and AT (95% confidence interval: -192.3 to -45.9; p = 0.001; 95% confidence interval: -143.4 to -13.8: p = 0.018, respectively). Our findings indicated a negative relationship between reticulocyte count and peak VO2 or AT. The life span of reticulocytes was close to the period of transient decline in RBC function that occurred after high-intensity exercise; therefore, the changes in reticulocytes might be related to the decline in exercise performance owing to this decline in RBC function.